Fruit Fly, Anastrepha nigrifascia Stone (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr. (EDIS)
Anastrepha nigrifascia Stone is one of six species of fruit flies of the genus Anastrepha which occur in Florida or which have been established in Florida at some time. This species appears to have a very restricted distribution, occurring only in the Florida Keys of Monroe County. It seldom has been collected and is not considered to be of economic importance. This document is EENY-262 (originally published as DPI Entomology Circular 66), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.